DOI: 10.14264/uql.2016.191
|View full text |Cite
|
Sign up to set email alerts
|

The effects of high voltage pulse treatment on ore characteristics and separation performances of a porphyry copper ore

Abstract: Technological advancement in large scale mining has changed little in the past 20 years.Increasing global energy demands and continuously decreasing ore grades are putting pressure on the mining industry to develop new, energy efficient technologies. Comminution has the highest energy consumption across the mining industry, and its energy demands continue to increase as finer grinding is required to liberate the valuable minerals in lower grade ores.Novel devices, such as high voltage pulse devices (HVP), have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The energy efficiency was determined to be relatively low attributed to the significant amount of energy loss for conversion of applied power into very narrow high voltage pulses besides the losses within the crushing chamber (Shuloyakov et al, 1995;Usov and Tsukerman, 2000). Recent research in JKMRC has also suggested lower efficiency for size reduction purposes using the selFrag Lab unit (Parker, 2015;Shi et al, 2014b;Wang et al, 2011). As an example, to produce the same extent of breakage on a Los Bronces porphyry Cu ore, it was reported that the selFrag machine consumed 21.8 kWh/t whereas the mechanical crushing method only used 1.5 kWh/t (Parker, 2015) to produce a -3.35 mm product from a nominal 10 mm feed size.…”
Section: Energy Consumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The energy efficiency was determined to be relatively low attributed to the significant amount of energy loss for conversion of applied power into very narrow high voltage pulses besides the losses within the crushing chamber (Shuloyakov et al, 1995;Usov and Tsukerman, 2000). Recent research in JKMRC has also suggested lower efficiency for size reduction purposes using the selFrag Lab unit (Parker, 2015;Shi et al, 2014b;Wang et al, 2011). As an example, to produce the same extent of breakage on a Los Bronces porphyry Cu ore, it was reported that the selFrag machine consumed 21.8 kWh/t whereas the mechanical crushing method only used 1.5 kWh/t (Parker, 2015) to produce a -3.35 mm product from a nominal 10 mm feed size.…”
Section: Energy Consumptionmentioning
confidence: 99%
“…Recent research in JKMRC has also suggested lower efficiency for size reduction purposes using the selFrag Lab unit (Parker, 2015;Shi et al, 2014b;Wang et al, 2011). As an example, to produce the same extent of breakage on a Los Bronces porphyry Cu ore, it was reported that the selFrag machine consumed 21.8 kWh/t whereas the mechanical crushing method only used 1.5 kWh/t (Parker, 2015) to produce a -3.35 mm product from a nominal 10 mm feed size. As for preweakening purposes, specific energy inputs between 1 -3 kWh/t were usually applied to induce cracks/microcracks inside the particles using the selFrag lab (Shi et al, 2012;van der Wielen et al, 2014;Wang et al, 2011).…”
Section: Energy Consumptionmentioning
confidence: 99%